Evoluţia drepturilor, libertăţilor şi îndatoririlor omului din domeniul mediului - Grama, Dumitru; Vlaicu, Vlad; Costache, Gheorghe (My University, 2007)
The existence of the human rights, liberties, and obligations in the domain of the environment is mentioned from the oldest times, before the appearance of the states, and even before the appearance of the law. The studies show that the first rights, liberties, and obligations settled the relations between the human being and they referred to hunting, fishing, to the protection of fire, to defense, etc. The studies also show that namely the law appeared as a necessity to settle the relations between the human being and the environment he lives in.